Structural Basis of Dimerization-dependent Ubiquitination by the SCF(Fbx4) Ubiquitin Ligase - Li, Yunfeng (American Society for Biochemistry and Molecular Biology, 2010)
The F-box proteins are the substrate recognition subunits of the SCF (Skp1-Cul1-Rbx1-F- box protein) ubiquitin ligase complexes that control the stability of numerous regulators in eukaryotic cells. Here we show that dimerization of the F-box protein Fbx4 is essential for SCF(Fbx4) (the superscript denotes the F-box protein) ubiquitination activity toward the telomere regulator Pin2 (also known as TRF1). The crystal structure of Fbx4 in complex with an adaptor protein Skp1 reveals an antiparallel dimer configuration in which the linker domain of Fbx4 interacts with the C-terminal substrate-binding domain of the other protomer, whereas the C-terminal domain of the protein adopts a compact α/β fold distinct from those of known F-box proteins. Biochemical studies indicate that both the N-terminal domain and a loop connecting the linker and C-terminal domain of Fbx4 are critical for the dimerization and activation of the protein. Our findings provide a framework for understanding the role of F-box dimerization in the SCF-mediated ubiquitination reaction.